Consumption and use of water in freshwater fish slaughterhouses (Research, Society and Development, 2022)
The rational use of water in productive activities has been the relevant factor for food production. The consumption of water in the industrialization of cattle, pigs and poultry is known in the literature, and it is necessary to expand the studies for the industrialization of fish. This study aimed to evaluate the average water consumption in the production processes in the industrialization of tilapia fillet, in small freshwater fish slaughterhouses. In this work, the treatment of effluents and the characteristics of the water resources used were also analyzed. Semi-structured interviews and visits to establishments were conducted in fifteen slaughterhouses in the western region of Paraná. The establishments evaluated were divided into groups according to their physical structure and the seal of the health inspection system for products of animal origin. The results point to the average need of 19.64 liters of water to produce 1 kg of tilapia fillet. In general, the effluents are not monitored, requiring improvements in the waste treatment process, avoiding environmental impacts derived from the industrialization of tilapia.